Preparation method of silicon-based composite conductive negative electrode and all-solid-state battery
By adding conductive graphite, single-walled carbon nanotubes and LiBH4 to the silicon-based negative electrode and using a specific ball mill mixing sequence to form a uniform ion-electron transmission network, the problem of poor rate performance and cycle stability of the silicon-based negative electrode is solved, and the high rate performance and cycle stability of the all-solid-state battery are achieved.
Patent Information
- Application Number
- CN202510397292.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-01
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-04-01
AI Technical Summary
The silicon-based negative electrode has poor rate performance and cycle stability in lithium-ion batteries, mainly due to mechanical stress caused by volume changes and low intrinsic conductivity limit the transmission of electrons and lithium ions.
By adding conductive graphite, single-walled carbon nanotubes and LiBH4 to the silicon-based anode and adopting a specific ball mill mixing sequence, a uniform ion-electron transmission network is formed to improve the conductivity and mechanical flexibility of the anode.
It significantly improves the electron and ion transmission efficiency of silicon-based composite conductive negative electrodes, enhances the rate performance and cycle stability of all-solid-state batteries, and reduces capacity attenuation.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a method for preparing a silicon-based composite conductive negative electrode and an all-solid-state battery. Background Art
[0002] Lithium-ion batteries have performed well in the fields of consumer electronics and electric vehicles, and have gradually become a key technology for energy storage grids. Compared with traditional liquid lithium-ion batteries, solid-state lithium batteries have higher stability, safety and energy density, and their development is an important direction for future research.
[0003] At present, among all kinds of negative electrode materials for solid-state lithium batteries, silicon has attracted much attention due to its low alloying potential and theoretical capacity of up to 4200mAh / g. However, pure silicon faces multiple challenges as a battery material. First, during the lithiation and delithiation process, the volume of silicon changes significantly, causing the particles to continuously expand and shrink. This repeated mechanical stress not only produces a large irreversible capacity, but also reduces the first coulombic efficiency, affecting the overall performance of the battery. In addition, the low intrinsic conductivity of silicon limits the transmission speed of electrons and lithium ions, further affecting its rate performance and cycle stability. Therefore, although silicon has a high theoretical specific capacity, it is still difficult to meet the needs of high-performance batteries in practical applications.
[0004] The silicon negative electrode is inserted with lithium through the pre-lithiation technology (for example, patent CN117199330A adds Li 21 Si5) can alleviate the above-mentioned problems related to silicon negative electrodes. The pre-embedded lithium source can compensate for the lithium consumed by side reactions and the formation of the solid electrolyte interface (SEI) film, thereby improving the first cycle coulombic efficiency and cycle stability of the electrode to a certain extent, but its effect on improving the electron and ion transmission efficiency of the silicon negative electrode is limited, and it cannot effectively solve the problem of poor rate performance of the silicon negative electrode. Summary of the invention
[0005] In order to solve the technical problems of poor rate performance and cycle stability of silicon negative electrodes, the present invention provides a method for preparing a silicon-based composite conductive negative electrode and an all-solid-state battery. The preparation method of the present invention can make the prepared silicon-based composite conductive negative electrode have higher electron and ion transmission efficiency, thereby improving the rate performance and cycle stability of the all-solid-state battery.
[0006] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a method for preparing a silicon-based composite conductive negative electrode, comprising the following steps: S1: ball-milling and mixing conductive graphite with a particle size of 1 to 30 μm and single-walled carbon nanotubes with a length of 3 to 50 μm to obtain precursor I; S2: ball-milling the precursor I and the silicon-based negative electrode active material to obtain the precursor II; S3: Precursor II and LiBH4 are mixed by ball milling, and after forming, a silicon-based composite conductive negative electrode is obtained.
[0007] The silicon-based composite conductive negative electrode prepared by the present invention contains conductive graphite and single-walled carbon nanotubes, which can form a bridge through π-π interaction and van der Waals force, thereby forming a conductive network in the negative electrode. In addition, the particle size of the conductive graphite used in the present invention is similar to the length of the single-walled carbon nanotubes, which can improve the stability of the conductive network and help maintain a continuous conductive network during the deformation process of the silicon-based negative electrode active material.
[0008] In addition to conductive graphite and single-walled carbon nanotubes, the present invention also adds LiBH4 to the silicon-based negative electrode, which can reduce the interface side reaction between the hydride solid electrolyte and the silicon-based negative electrode in the solid-state battery, thereby avoiding the rapid increase of battery impedance and the rapid decay of capacity during the cycle. At the same time, the elastic modulus of the hydride solid electrolyte is low, and it has good mechanical flexibility, which can adapt to the deformation and stress of the silicon-based negative electrode during the charge and discharge process, thereby reducing the particle breakage of the silicon-based negative electrode during the cycle, improving the cycle stability of the battery, and reducing its cycle capacity decay. In addition, LiBH4 also has a high ionic conductivity, which can improve the transmission efficiency of lithium ions in the silicon-based negative electrode.
[0009] On this basis, in order to give full play to the role of conductive graphite, single-walled carbon nanotubes and LiBH4 to a greater extent, the present invention has specially designed the mixing order according to the characteristics of these additives. Specifically: the present invention first ball-mills the conductive graphite and single-walled carbon nanotubes with the silicon-based negative electrode active material, and then ball-mills them with LiBH4, so that a uniform ion-electron transmission network can be formed in the prepared negative electrode; if the above four components are ball-milled and mixed in one step without any particular order, or the conductive graphite and single-walled carbon nanotubes are first ball-milled and mixed with LiBH4, and then ball-milled and mixed with the silicon-based negative electrode active material, then due to the difference in electronegativity of the material atoms, the conductive graphite and single-walled carbon nanotubes will preferentially interact with LiBH4, and two types of agglomerates of conductive graphite + single-walled carbon nanotubes + LiBH4 and silicon-based negative electrode active materials are formed microscopically, which is not conducive to the construction of a uniform ion-electron transmission network in the negative electrode.
[0010] Preferably, in step S1, the length of the single-walled carbon nanotubes and the particle size of the conductive graphite are both 5-20 μm.
[0011] Preferably, in step S1, the diameter of the single-walled carbon nanotube is 1-2 nm; and the mass ratio of the single-walled carbon nanotube to the conductive graphite is 0.11-9:1.
[0012] Preferably, in step S2, the silicon-based negative electrode active material is Li x One or both of Si alloy material and Al / LiH / Li / Si composite material.
[0013] Compared with pure Si negative electrode active materials, Li x In Si alloy materials and Al / LiH / Li / Si composite materials, the introduction of Li can compensate for the lithium loss caused by side reactions, thereby improving the cycle stability of all-solid-state batteries. In addition, Al / LiH / Li / Si composite materials introduce Al and LiH at the same time as Li, among which: Al can improve the conductivity of the silicon-based negative electrode, thereby further improving the cycle performance and rate performance of the battery; the electric field effect between LiH and the Li-Al alloy and Li-Si alloy in the negative electrode can improve the lithium ion transmission efficiency in the negative electrode and balance the electric field on the surface of the alloy material, thereby avoiding the growth of lithium dendrites induced by the local potential on the surface of the material, which can further improve the cycle stability of the all-solid-state battery and reduce the cycle capacity attenuation.
[0014] Preferably, in step S2, in the silicon-based negative electrode active material, the molar ratio of Li to Si is 2.3-4.4:1 (Li in the molar ratio does not include Li in LiH).
[0015] Preferably, the preparation step of the Al / LiH / Li / Si composite material comprises: under vacuum or inert atmosphere, heating a mixture of silicon and lithium aluminum hydride (LiAlH4) in a molar ratio of 2-8:1 to 160-190°C for 3-6 hours, then heating to 200-300°C for 2-5 hours, and then mixing with Li and heat treating at 200-300°C for 2-4 hours.
[0016] In the preparation process of the above Al / LiH / Li / Si composite material, heating at 160-190℃ for 3-6h can decompose LiAlH4 into Li3AlH6, Al and H2; and then heating at 200-300℃ for 2-5h can further decompose Li3AlH6 into LiH, Al and H2. This two-step thermal decomposition method can form highly dispersed nano-aluminum particles and nano-LiH particles in situ between silicon particles. Among them, highly dispersed nano-aluminum particles help to achieve higher alloying / de-alloying reaction reversibility, thereby improving the cycle stability of all-solid-state batteries to a greater extent; highly dispersed nano-LiH particles can reduce the local potential difference at each point on the surface of Li-Al alloy and Li-Si alloy, which helps to improve the lithium ion transmission efficiency by utilizing the electric field effect between LiH particles and Li-Al alloy and Li-Si alloy, thereby achieving better battery cycle stability.
[0017] In the Al / LiH / Li / Si composite material, when the doping amount of Al and LiH is too low, the cycle stability of the all-solid-state battery cannot be effectively improved, and even the cycle stability may be reduced. In the preparation process of the Al / LiH / Li / Si composite material, the molar ratio of silicon to lithium aluminum hydride is designed to be 2~8:1, which can effectively improve the cycle stability of the all-solid-state battery. In addition, in the preparation process of the entire Al / LiH / Li / Si composite material, the temperature of the heat treatment in each stage is not higher than 300°C, which can prevent LiH from further decomposing into Li, which is conducive to better controlling the doping amount of LiH in the negative electrode and realizing the improvement of the cycle stability of the all-solid-state battery.
[0018] Preferably, the step of preparing the mixture of silicon and lithium aluminum hydride comprises: grinding and mixing silicon and lithium aluminum hydride, and then performing high-energy ball milling; the conditions of the high-energy ball milling are as follows: the ball-to-material ratio is 60-120:1, the rotation speed is 200-500rpm, and the time is 1-5h.
[0019] Preferably, the mixing method with Li is ball milling, and the conditions are as follows: ball-to-material ratio is 60-120:1, rotation speed is 100-200 rpm, and time is 30-60 min.
[0020] Preferably, the mass ratio of the silicon-based negative electrode active material, the first precursor material and the solid electrolyte is 50-80:10-25:10-25.
[0021] Preferably, in steps S1 to S3, the conditions for ball milling are as follows: a ball-to-material ratio of 60 to 120:1, a rotation speed of 100 to 1200 rpm, and a time of 2 to 30 hours.
[0022] Preferably, in step S3, the molding method is: compression molding on one side of the solid electrolyte sheet.
[0023] In a second aspect, the present invention provides an all-solid-state battery, comprising a silicon-based composite conductive negative electrode prepared by the preparation method.
[0024] Preferably, the all-solid-state battery comprises a positive electrode, a hydride solid electrolyte sheet and a silicon-based composite conductive negative electrode stacked in sequence; the positive electrode comprises a positive electrode active material, a conductive agent and a hydride solid electrolyte, and the positive electrode active material comprises one or more of S, Se, Li2S, Li2Se and sulfide polyacrylonitrile (SPAN).
[0025] Compared with the prior art, the present invention has the following advantages: (1) The present invention adds conductive graphite, single-walled carbon nanotubes and LiBH4 to the silicon-based negative electrode, and cooperates with a specific preparation method to form a uniform ion-electron transmission network in the silicon-based negative electrode, thereby giving the all-solid-state battery better rate performance and cycle stability.
[0026] (2) The present invention uses Al / LiH / Li / Si composite materials as negative electrode active materials. By doping Al and LiH therein, the cycle stability of the all-solid-state battery can be further improved. Furthermore, by adopting a specific method to prepare the Al / LiH / Li / Si composite materials, the battery cycle performance can be improved to a higher level. DETAILED DESCRIPTION
[0027] The present invention will be further described below in conjunction with the embodiments.
[0028] A method for preparing a silicon-based composite conductive negative electrode comprises the following steps: S1: ball-milling and mixing conductive graphite with a particle size of 1 to 30 μm and single-walled carbon nanotubes with a length of 3 to 50 μm to obtain precursor I; S2: ball-milling the precursor I and the silicon-based negative electrode active material to obtain the precursor II; S3: Precursor II and LiBH4 are mixed by ball milling, and after forming, a silicon-based composite conductive negative electrode is obtained.
[0029] As a specific implementation, the mass ratio of the silicon-based negative electrode active material, the first precursor material and the solid electrolyte is 50~80:10~25:10~25.
[0030] As a specific implementation, in step S1, the length of the single-walled carbon nanotube and the particle size of the conductive graphite are both 5-20 μm.
[0031] As a specific implementation, in step S1, the diameter of the single-walled carbon nanotube is 1-2 nm; and the mass ratio between the single-walled carbon nanotube and the conductive graphite is 0.11-9:1.
[0032] As a specific embodiment, in step S2, the silicon-based negative electrode active material is Li x One or two of a Si alloy material and an Al / LiH / Li / Si composite material, wherein the molar ratio of Li to Si is 2.3-4.4:1; the preparation steps of the Al / LiH / Li / Si composite material include: in a vacuum or inert atmosphere, heating a mixture of silicon and lithium aluminum hydride (LiAlH4) with a molar ratio of 2-8:1 to 160-190°C for 3-6 hours, then heating to 200-300°C for 2-5 hours, and then mixing with Li and heat treating at 200-300°C for 2-4 hours.
[0033] In the steps of preparing the Al / LiH / Li / Si composite material, optionally or preferably: The steps of preparing the mixture of silicon and lithium aluminum hydride include: grinding and mixing silicon and lithium aluminum hydride, and then performing high-energy ball milling; the conditions of the high-energy ball milling are as follows: the ball-to-material ratio is 60-120:1, the rotation speed is 200-500 rpm, and the time is 1-5 hours; The mixing method with Li is ball milling, and the conditions are as follows: the ball-to-material ratio is 60-120:1, the rotation speed is 100-200 rpm, and the time is 30-60 min.
[0034] As a specific implementation, in steps S1-S3, the conditions for ball milling mixing are as follows: ball-to-material ratio is 60-120:1, rotation speed is 100-1200 rpm, and time is 2-30 hours.
[0035] As a specific implementation, in step S3, the molding method is: compression molding on one side of the solid electrolyte sheet.
[0036] An all-solid-state battery comprises a silicon-based composite conductive negative electrode prepared by the preparation method.
[0037] As a specific implementation, the all-solid-state battery includes a positive electrode, a hydride solid electrolyte sheet and a silicon-based composite conductive negative electrode stacked in sequence; the positive electrode includes a positive electrode active material, a conductive agent and a hydride solid electrolyte, and the positive electrode active material includes one or more of S, Se, Li2S, Li2Se and sulfide polyacrylonitrile (SPAN).
[0038] The present invention is described below by specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Without departing from the spirit and scope of the inventive concept, changes and advantages that can be thought of by those skilled in the art are included in the present invention, and the attached claims and any equivalents thereof are the protection scope of the present invention.
[0039] Example 1 The silicon-based composite conductive negative electrode and the all-solid-state battery of this embodiment are prepared by the following steps: S1: Preparation of silicon-based composite conductive negative electrode materials Single-walled carbon nanotubes (length 5-20 μm, diameter 1-2 nm) and conductive graphite (particle size 5-20 μm) were mixed in a mass ratio of 1:1 and placed in a stainless steel ball mill. They were ball milled for 2 h in an argon atmosphere at a ball-to-material ratio of 100:1 and a rotation speed of 400 rpm to obtain precursor I. Then, Li 2 times the mass of precursor I was added to the stainless steel ball mill. 2.3The Si alloy material was ball-milled for 2 h in an argon atmosphere, at a ball-to-material ratio of 100:1 and a rotation speed of 400 rpm to obtain a precursor II. Finally, LiBH4 with a mass of 1 / 3 of the precursor II was added to a stainless steel ball milling jar, and ball-milled for 10 h in an argon atmosphere, at a ball-to-material ratio of 100:1 and a rotation speed of 600 rpm to obtain a silicon-based composite conductive negative electrode material.
[0040] S2: Preparation of all-solid-state batteries S, conductive carbon black (Super P) and LiBH4 were mixed in a mass ratio of 3:3:4 to obtain a positive electrode material. The hydride electrolyte LiBH4 was pressed into a sheet at a pressure of 300MPa to obtain a solid electrolyte sheet. The silicon-based composite conductive negative electrode material was pressed into a sheet at a pressure of 50MPa on one side of the solid electrolyte sheet to form a silicon-based composite conductive negative electrode. The positive electrode material was pressed into a sheet at a pressure of 50MPa on the other side of the solid electrolyte sheet to form a positive electrode, thereby obtaining an all-solid-state battery.
[0041] Example 2 The difference between this embodiment and embodiment 1 is that: Li 2.3 The Si alloy material is replaced with an Al / LiH / Li / Si composite material. Specifically, the silicon-based composite conductive negative electrode and the all-solid-state battery of this embodiment are prepared by the following steps: S1: Preparation of Al / LiH / Li / Si composite materials Silicon powder and lithium aluminum hydride powder were placed in a mortar at a molar ratio of 8:1, ground to make them uniformly mixed, and then transferred to a stainless steel ball mill, ball milled for 2 hours under argon atmosphere, ball to material ratio of 100:1, and rotation speed of 400rpm to obtain Si / LiAlH4 mixed material. The Si / LiAlH4 mixed material was transferred to a stainless steel tube, and the vacuum degree in the tube was maintained at not less than 10kPa during the subsequent heat treatment. The temperature was raised to 160℃ and maintained for 6 hours, and then continued to rise to 300℃ and maintained for 2 hours, and then cooled to room temperature to obtain Al / LiH / Si composite material. Lithium powder with a molar weight of 2.3 times that of silicon powder was weighed, and placed in a stainless steel ball mill together with the Al / LiH / Si composite material. After ball milling for 40 minutes under argon atmosphere, ball to material ratio of 100:1, and rotation speed of 100rpm, it was transferred to a stainless steel tube, heated to 300℃ and maintained for 3 hours under argon atmosphere to obtain Al / LiH / Li / Si composite material.
[0042] S2: Preparation of silicon-based composite conductive negative electrode materials Single-walled carbon nanotubes (length 5~20μm, diameter 1~2nm) and conductive graphite (particle size 5~20μm) were mixed in a mass ratio of 1:1, placed in a stainless steel ball mill, and ball milled for 2h under argon atmosphere, ball-to-material ratio of 100:1, and rotation speed of 400rpm to obtain precursor I. Then, Al / LiH / Li / Si composite material with a mass twice that of precursor I was added to the stainless steel ball mill, and ball milling was continued for 2h under argon atmosphere, ball-to-material ratio of 100:1, and rotation speed of 400rpm to obtain precursor II. Finally, LiBH4 with a mass of 1 / 3 of precursor II was added to the stainless steel ball mill, and ball milling was carried out for 10h under argon atmosphere, ball-to-material ratio of 100:1, and rotation speed of 600rpm to obtain silicon-based composite conductive negative electrode material.
[0043] S3: Preparation of all-solid-state batteries S, conductive carbon black (Super P) and LiBH4 were mixed in a mass ratio of 3:3:4 to obtain a positive electrode material. The hydride electrolyte LiBH4 was pressed into a sheet at a pressure of 300MPa to obtain a solid electrolyte sheet. The silicon-based composite conductive negative electrode material was pressed into a sheet at a pressure of 50MPa on one side of the solid electrolyte sheet to form a silicon-based composite conductive negative electrode. The positive electrode material was pressed into a sheet at a pressure of 50MPa on the other side of the solid electrolyte sheet to form a positive electrode, thereby obtaining an all-solid-state battery.
[0044] Example 3 The difference between this embodiment and embodiment 1 is that: Li 2.3 The Si alloy material is replaced with an Al / LiH / Li / Si composite material. Specifically, the silicon-based composite conductive negative electrode and the all-solid-state battery of this embodiment are prepared by the following steps: S1: Preparation of Al / LiH / Li / Si composite materials Silicon powder and lithium aluminum hydride powder were placed in a mortar at a molar ratio of 2:1, ground to make them uniformly mixed, and then transferred to a stainless steel ball mill, ball milled for 2 hours under argon atmosphere, ball-to-material ratio of 100:1, and rotation speed of 400rpm to obtain Si / LiAlH4 mixed material. The Si / LiAlH4 mixed material was transferred to a stainless steel tube, and the vacuum degree in the tube was maintained at not less than 10kPa during the subsequent heat treatment. The temperature was raised to 180℃ and maintained for 3 hours, and then continued to rise to 210℃ and maintained for 5 hours, and then cooled to room temperature to obtain Al / LiH / Si composite material. Lithium powder with a molar weight of 2.3 times that of silicon powder was weighed, and placed in a stainless steel ball mill together with the Al / LiH / Si composite material. After ball milling for 40 minutes under argon atmosphere, ball-to-material ratio of 100:1, and rotation speed of 100rpm, it was transferred to a stainless steel tube, heated to 300℃ and maintained for 3 hours under argon atmosphere to obtain Al / LiH / Li / Si composite material.
[0045] S2: Preparation of silicon-based composite conductive negative electrode materials Single-walled carbon nanotubes (length 5~20μm, diameter 1~2nm) and conductive graphite (particle size 5~20μm) were mixed in a mass ratio of 1:1, placed in a stainless steel ball mill, and ball milled for 2h under argon atmosphere, ball-to-material ratio of 100:1, and rotation speed of 400rpm to obtain precursor I. Then, Al / LiH / Li / Si composite material with a mass twice that of precursor I was added to the stainless steel ball mill, and ball milling was continued for 2h under argon atmosphere, ball-to-material ratio of 100:1, and rotation speed of 400rpm to obtain precursor II. Finally, LiBH4 with a mass of 1 / 3 of precursor II was added to the stainless steel ball mill, and ball milling was carried out for 10h under argon atmosphere, ball-to-material ratio of 100:1, and rotation speed of 600rpm to obtain silicon-based composite conductive negative electrode material.
[0046] S3: Preparation of all-solid-state batteries S, conductive carbon black (Super P) and LiBH4 were mixed in a mass ratio of 3:3:4 to obtain a positive electrode material. The hydride electrolyte LiBH4 was pressed into a sheet at a pressure of 300MPa to obtain a solid electrolyte sheet. The silicon-based composite conductive negative electrode material was pressed into a sheet at a pressure of 50MPa on one side of the solid electrolyte sheet to form a silicon-based composite conductive negative electrode. The positive electrode material was pressed into a sheet at a pressure of 50MPa on the other side of the solid electrolyte sheet to form a positive electrode, thereby obtaining an all-solid-state battery.
[0047] Example 4 The difference between this embodiment and embodiment 2 is that the molar ratio of silicon powder to lithium aluminum hydride powder is changed from 8:1 to 18:1. Specifically, the silicon-based composite conductive negative electrode and the all-solid-state battery of this embodiment are prepared by the following steps: S1: Preparation of Al / LiH / Li / Si composite materials Silicon powder and lithium aluminum hydride powder were placed in a mortar at a molar ratio of 18:1, ground to make them uniformly mixed, and then transferred to a stainless steel ball mill, ball milled for 2 hours under argon atmosphere, ball to material ratio of 100:1, and rotation speed of 400rpm to obtain Si / LiAlH4 mixed material. The Si / LiAlH4 mixed material was transferred to a stainless steel tube, and the vacuum degree in the tube was maintained at not less than 10kPa during the subsequent heat treatment. The temperature was raised to 160℃ and maintained for 6 hours, and then continued to rise to 300℃ and maintained for 2 hours, and then cooled to room temperature to obtain Al / LiH / Si composite material. Lithium powder with a molar weight of 2.3 times that of silicon powder was weighed, and placed in a stainless steel ball mill together with the Al / LiH / Si composite material. After ball milling for 40 minutes under argon atmosphere, ball to material ratio of 100:1, and rotation speed of 100rpm, it was transferred to a stainless steel tube, heated to 300℃ and maintained for 3 hours under argon atmosphere to obtain Al / LiH / Li / Si composite material.
[0048] S2: Preparation of silicon-based composite conductive negative electrode materials Single-walled carbon nanotubes (length 5~20μm, diameter 1~2nm) and conductive graphite (particle size 5~20μm) were mixed in a mass ratio of 1:1, placed in a stainless steel ball mill, and ball milled for 2h under argon atmosphere, ball-to-material ratio of 100:1, and rotation speed of 400rpm to obtain precursor I. Then, Al / LiH / Li / Si composite material with a mass twice that of precursor I was added to the stainless steel ball mill, and ball milling was continued for 2h under argon atmosphere, ball-to-material ratio of 100:1, and rotation speed of 400rpm to obtain precursor II. Finally, LiBH4 with a mass of 1 / 3 of precursor II was added to the stainless steel ball mill, and ball milling was carried out for 10h under argon atmosphere, ball-to-material ratio of 100:1, and rotation speed of 600rpm to obtain silicon-based composite conductive negative electrode material.
[0049] S3: Preparation of all-solid-state batteries S, conductive carbon black (Super P) and LiBH4 were mixed in a mass ratio of 3:3:4 to obtain a positive electrode material. The hydride electrolyte LiBH4 was pressed into a sheet at a pressure of 300MPa to obtain a solid electrolyte sheet. The silicon-based composite conductive negative electrode material was pressed into a sheet at a pressure of 50MPa on one side of the solid electrolyte sheet to form a silicon-based composite conductive negative electrode. The positive electrode material was pressed into a sheet at a pressure of 50MPa on the other side of the solid electrolyte sheet to form a positive electrode, thereby obtaining an all-solid-state battery.
[0050] Example 5 The difference between this embodiment and embodiment 2 is that in step S1, LiAlH4 is decomposed into Al and LiH by a one-step thermal decomposition method. Specifically, the silicon-based composite conductive negative electrode and the all-solid-state battery of this embodiment are prepared by the following steps: S1: Preparation of Al / LiH / Li / Si composite materials Silicon powder and lithium aluminum hydride powder were placed in a mortar at a molar ratio of 8:1, ground to make them uniformly mixed, and then transferred to a stainless steel ball mill, ball milled for 2 hours under argon atmosphere, ball-to-material ratio of 100:1, and rotation speed of 400rpm to obtain Si / LiAlH4 mixed material. The Si / LiAlH4 mixed material was transferred to a stainless steel tube, and the vacuum degree in the tube was maintained at not less than 10kPa during the subsequent heat treatment, and the temperature was raised to 300℃ for 8 hours, and then cooled to room temperature to obtain Al / LiH / Si composite material. Lithium powder with a molar weight of 2.3 times that of silicon powder was weighed, and placed in a stainless steel ball mill together with the Al / LiH / Si composite material, ball milled for 40 minutes under argon atmosphere, ball-to-material ratio of 100:1, and rotation speed of 100rpm, and then transferred to a stainless steel tube, heated to 300℃ for 3 hours under argon atmosphere to obtain Al / LiH / Li / Si composite material.
[0051] S2: Preparation of silicon-based composite conductive negative electrode materials Single-walled carbon nanotubes (length 5~20μm, diameter 1~2nm) and conductive graphite (particle size 5~20μm) were mixed in a mass ratio of 1:1, placed in a stainless steel ball mill, and ball milled for 2h under argon atmosphere, ball-to-material ratio of 100:1, and rotation speed of 400rpm to obtain precursor I. Then, Al / LiH / Li / Si composite material with a mass twice that of precursor I was added to the stainless steel ball mill, and ball milling was continued for 2h under argon atmosphere, ball-to-material ratio of 100:1, and rotation speed of 400rpm to obtain precursor II. Finally, LiBH4 with a mass of 1 / 3 of precursor II was added to the stainless steel ball mill, and ball milling was carried out for 10h under argon atmosphere, ball-to-material ratio of 100:1, and rotation speed of 600rpm to obtain silicon-based composite conductive negative electrode material.
[0052] S3: Preparation of all-solid-state batteries S, conductive carbon black (Super P) and LiBH4 were mixed in a mass ratio of 3:3:4 to obtain a positive electrode material. The hydride electrolyte LiBH4 was pressed into a sheet at a pressure of 300MPa to obtain a solid electrolyte sheet. The silicon-based composite conductive negative electrode material was pressed into a sheet at a pressure of 50MPa on one side of the solid electrolyte sheet to form a silicon-based composite conductive negative electrode. The positive electrode material was pressed into a sheet at a pressure of 50MPa on the other side of the solid electrolyte sheet to form a positive electrode, thereby obtaining an all-solid-state battery.
[0053] Example 6 The difference between this embodiment and embodiment 2 is that in step S2, the temperature of the second stage thermal decomposition of LiAlH4 is changed from 300°C to 450°C. Specifically, the silicon-based composite conductive negative electrode and the all-solid-state battery of this embodiment are prepared by the following steps: S1: Preparation of Al / LiH / Li / Si composite materials Silicon powder and lithium aluminum hydride powder were placed in a mortar at a molar ratio of 8:1, ground to make them uniformly mixed, and then transferred to a stainless steel ball mill, ball milled for 2 hours under argon atmosphere, ball-to-material ratio of 100:1, and rotation speed of 400rpm to obtain Si / LiAlH4 mixed material. The Si / LiAlH4 mixed material was transferred to a stainless steel tube, and the vacuum degree in the tube was maintained at not less than 10kPa during the subsequent heat treatment. The temperature was raised to 160℃ and maintained for 6 hours, and then continued to rise to 450℃ and maintained for 2 hours, and then cooled to room temperature to obtain Al / LiH / Si composite material. Lithium powder with a molar weight of 2.3 times that of silicon powder was weighed, and placed in a stainless steel ball mill together with the Al / LiH / Si composite material. After ball milling for 40 minutes under argon atmosphere, ball-to-material ratio of 100:1, and rotation speed of 100rpm, it was transferred to a stainless steel tube, heated to 300℃ and maintained for 3 hours under argon atmosphere to obtain Al / LiH / Li / Si composite material.
[0054] S2: Preparation of silicon-based composite conductive negative electrode materials Single-walled carbon nanotubes (length 5~20μm, diameter 1~2nm) and conductive graphite (particle size 5~20μm) were mixed in a mass ratio of 1:1, placed in a stainless steel ball mill, and ball milled for 2h under argon atmosphere, ball-to-material ratio of 100:1, and rotation speed of 400rpm to obtain precursor I. Then, Al / LiH / Li / Si composite material with a mass twice that of precursor I was added to the stainless steel ball mill, and ball milling was continued for 2h under argon atmosphere, ball-to-material ratio of 100:1, and rotation speed of 400rpm to obtain precursor II. Finally, LiBH4 with a mass of 1 / 3 of precursor II was added to the stainless steel ball mill, and ball milling was carried out for 10h under argon atmosphere, ball-to-material ratio of 100:1, and rotation speed of 600rpm to obtain silicon-based composite conductive negative electrode material.
[0055] S3: Preparation of all-solid-state batteries S, conductive carbon black (Super P) and LiBH4 were mixed in a mass ratio of 3:3:4 to obtain a positive electrode material. The hydride electrolyte LiBH4 was pressed into a sheet at a pressure of 300MPa to obtain a solid electrolyte sheet. The silicon-based composite conductive negative electrode material was pressed into a sheet at a pressure of 50MPa on one side of the solid electrolyte sheet to form a silicon-based composite conductive negative electrode. The positive electrode material was pressed into a sheet at a pressure of 50MPa on the other side of the solid electrolyte sheet to form a positive electrode, thereby obtaining an all-solid-state battery.
[0056] Comparative Example 1 The difference between this comparative example and Example 1 is that the single-walled carbon nanotube (length 5-20 μm, diameter 1-2 nm) is replaced with a single-walled carbon nanotube (length 1-2 μm, diameter 1-2 nm). Specifically, the silicon-based composite conductive negative electrode and the all-solid-state battery of this comparative example are prepared by the following steps: S1: Preparation of silicon-based composite conductive negative electrode materials Single-walled carbon nanotubes (length 1~2μm, diameter 1~2nm) and conductive graphite (particle size 5~20μm) were mixed in a mass ratio of 1:1 and placed in a stainless steel ball mill. They were ball milled for 2h under an argon atmosphere, a ball-to-material ratio of 100:1, and a rotation speed of 400rpm to obtain precursor I. Then, Li 2 times the mass of precursor I was added to the stainless steel ball mill. 2.3 The Si alloy material was ball-milled for 2 h in an argon atmosphere, at a ball-to-material ratio of 100:1 and a rotation speed of 400 rpm to obtain a precursor II. Finally, LiBH4 with a mass of 1 / 3 of the precursor II was added to a stainless steel ball milling jar, and ball-milled for 10 h in an argon atmosphere, at a ball-to-material ratio of 100:1 and a rotation speed of 600 rpm to obtain a silicon-based composite conductive negative electrode material.
[0057] S2: Preparation of all-solid-state batteries S, conductive carbon black (Super P) and LiBH4 were mixed in a mass ratio of 3:3:4 to obtain a positive electrode material. The hydride electrolyte LiBH4 was pressed into a sheet at a pressure of 300MPa to obtain a solid electrolyte sheet. The silicon-based composite conductive negative electrode material was pressed into a sheet at a pressure of 50MPa on one side of the solid electrolyte sheet to form a silicon-based composite conductive negative electrode. The positive electrode material was pressed into a sheet at a pressure of 50MPa on the other side of the solid electrolyte sheet to form a positive electrode, thereby obtaining an all-solid-state battery.
[0058] Comparative Example 2 The difference between this comparative example and Example 1 is that in step S1, single-walled carbon nanotubes, conductive graphite, Li 2.3 The Si alloy material and LiBH4 are mixed by ball milling in one step. Specifically, the silicon-based composite conductive negative electrode and the all-solid-state battery of this comparative example are prepared by the following steps: S1: Preparation of silicon-based composite conductive negative electrode materials Single-walled carbon nanotubes (length 5~20μm, diameter 1~2nm), conductive graphite (particle size 5~20μm), Li 2.3 The Si alloy material and LiBH4 were mixed in a mass ratio of 1:1:4:2, placed in a stainless steel ball mill, and ball milled for 10 hours in an argon atmosphere, with a ball-to-material ratio of 100:1 and a rotation speed of 600 rpm to obtain a silicon-based composite conductive negative electrode material.
[0059] S2: Preparation of all-solid-state batteries S, conductive carbon black (Super P) and LiBH4 were mixed in a mass ratio of 3:3:4 to obtain a positive electrode material. The hydride electrolyte LiBH4 was pressed into a sheet at a pressure of 300MPa to obtain a solid electrolyte sheet. The silicon-based composite conductive negative electrode material was pressed into a sheet at a pressure of 50MPa on one side of the solid electrolyte sheet to form a silicon-based composite conductive negative electrode. The positive electrode material was pressed into a sheet at a pressure of 50MPa on the other side of the solid electrolyte sheet to form a positive electrode, thereby obtaining an all-solid-state battery.
[0060] Test Case The all-solid-state batteries prepared in each embodiment and comparative example were tested for performance according to the following method: (1) Cycle performance: After 50 cycles of charge and discharge at a temperature of 120°C, a charge and discharge current of 0.1C, and a pressure of 50 MPa, the initial coulombic efficiency and the capacity retention rate after 50 cycles were tested.
[0061] (2) Rate performance: The battery was charged at a current of 0.1C and discharged at currents of 0.1C, 0.2C, 0.5C, 1C, and 2C, respectively. The charge cut-off voltage was 3V and the discharge cut-off voltage was 0.1V. The discharge specific capacity was tested at different discharge currents.
[0062] The performance test results of all-solid-state batteries are shown in Table 1.
[0063] Table 1 Performance test results of all-solid-state batteries
[0064] Analyzing the test results in Table 1, we can see that: (1) The first coulombic efficiency, cycle stability and rate performance of the all-solid-state battery of Example 1 are better than those of Comparative Example 1. The reason for this is that the length of the single-walled carbon nanotubes used in Example 1 is similar to the particle size of the conductive graphite, which can make the constructed conductive network more stable and help maintain a continuous conductive network during the deformation process of the negative electrode active material.
[0065] (2) The first coulombic efficiency, cycle stability and rate performance of the all-solid-state battery of Example 1 are better than those of Comparative Example 2. The reason is that: Comparative Example 2 combines single-walled carbon nanotubes, conductive graphite, and Li 2.3 Si alloy material and LiBH4 are mixed by ball milling in one step in no particular order. Due to the difference in electronegativity of material atoms, conductive graphite and single-walled carbon nanotubes will preferentially interact with LiBH4, forming two types of agglomerates of conductive graphite + single-walled carbon nanotubes + LiBH4 and silicon-based negative electrode active materials at the microscopic level, which is not conducive to the construction of a uniform ion-electron transport network throughout the negative electrode.
[0066] (3) The cycle stability and rate performance of the all-solid-state batteries of Examples 2 and 3 are better than those of Example 1. The reasons are as follows: Al and LiH are doped into the silicon-based negative electrode active materials used in Examples 2 and 3, wherein Al can improve the conductivity of the silicon-based negative electrode, thereby further improving the cycle performance and rate performance of the battery; the electric field effect between LiH and the Li-Al alloy and Li-Si alloy in the negative electrode can improve the lithium ion transmission efficiency in the negative electrode and balance the electric field on the surface of the alloy material, thereby avoiding the growth of lithium dendrites induced by the local potential on the surface of the material, which can further improve the cycle stability of the all-solid-state battery and reduce the cycle capacity attenuation.
[0067] (4) The cycle stability and rate performance of the all-solid-state battery of Example 4 are worse than those of Example 2, and lower than those of Example 1. This indicates that when the amount of LiAlH4 used is too small, the doping amount of Al and LiH in the silicon-based negative electrode active material is too small, which will cause the battery cycle stability and rate performance to decrease.
[0068] (5) The cycle stability and rate performance of the all-solid-state battery of Example 5 are lower than those of Example 2 and Example 1. The reason for this is that in the process of preparing the Al / LiH / Li / Si composite material in Example 5, LiAlH4 is decomposed into Al and LiH by a one-step thermal decomposition method, and the size of the formed LiH particles is relatively large, which will lead to a large local potential difference between the points on the surface of the Li-Al alloy and the Li-Si alloy, and the lithium ion transmission efficiency in the negative electrode is low. Even in the system of the present invention, the battery cycle stability and rate performance will be lower than that without the introduction of Al and LiH.
[0069] (6) The cycle stability of the all-solid-state battery of Example 6 is lower than that of Example 2 and lower than that of Example 1. The reason for this is that in the process of preparing the Al / LiH / Li / Si composite material in Example 6, an excessively high heat treatment temperature is used, which will further decompose LiH into Li, and the electric field effect between LiH and the Li-Al alloy and Li-Si alloy in the negative electrode cannot be used to promote lithium ion transmission, balance the electric field on the surface of the alloy material, and reduce lithium dendrite growth. Even in the system of the present invention, the battery cycle stability and rate performance will be lower than that without the introduction of Al and LiH.
[0070] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0071] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a silicon-based composite conductive negative electrode, characterized in that: The following steps are involved: S1: ball-milling and mixing conductive graphite with a particle size of 1 to 30 μm and single-walled carbon nanotubes with a length of 3 to 50 μm to obtain precursor I; S2: ball-milling the precursor I and the silicon-based negative electrode active material to obtain the precursor II; S3: Precursor II and LiBH4 are mixed by ball milling, and after forming, a silicon-based composite conductive negative electrode is obtained.
2. The preparation method according to claim 1, characterized in that: In step S1, the diameter of the single-walled carbon nanotube is 1-2 nm; and the mass ratio between the single-walled carbon nanotube and the conductive graphite is 0.11-9:
1.
3. The preparation method according to claim 1, characterized in that: In step S2, the silicon-based negative electrode active material is Li x One or both of Si alloy material and Al / LiH / Li / Si composite material.
4. The preparation method according to claim 3, characterized in that: In step S2, in the silicon-based negative electrode active material, the molar ratio between Li and Si is 2.3-4.4:
1.
5. The preparation method according to claim 3 or 4, characterized in that: The preparation steps of the Al / LiH / Li / Si composite material include: in a vacuum or inert atmosphere, heating a mixture of silicon and lithium aluminum hydride in a molar ratio of 2-8:1 to 160-190° C. and maintaining it for 3-6 hours, then heating it to 200-300° C. and maintaining it for 2-5 hours, and then mixing it with Li and heat treating it at 200-300° C. for 2-4 hours.
6. The preparation method according to claim 5, characterized in that: The mixing method with Li is ball milling, and the conditions are as follows: the ball-to-material ratio is 60-120:1, the rotation speed is 100-200 rpm, and the time is 30-60 min.
7. The preparation method according to claim 1, characterized in that: The mass ratio of the silicon-based negative electrode active material, the first precursor material and the solid electrolyte is 50-80:10-25:10-25.
8. The preparation method according to claim 1, characterized in that: In steps S1 to S3, the conditions for ball milling are as follows: ball-to-material ratio is 60 to 120:1, rotation speed is 100 to 1200 rpm, and time is 2 to 30 hours.
9. An all-solid-state battery, characterized in that: It comprises a silicon-based composite conductive negative electrode prepared by the preparation method according to any one of claims 1 to 8.
10. The all-solid-state battery according to claim 9, characterized in that: It includes a positive electrode, a hydride solid electrolyte sheet and a silicon-based composite conductive negative electrode stacked in sequence; the positive electrode includes a positive electrode active material, a conductive agent and a hydride solid electrolyte, and the positive electrode active material includes one or more of S, Se, Li2S, Li2Se and sulfide polyacrylonitrile.
Citation Information
Patent Citations
Preparation method of silicon negative electrode for high-first-effect long-cycle all-solid-state battery
CN117199330A
Preparation method for silicon / graphite / solid electrolyte composite negative electrode material
CN110858642A
Silicon-based composite material for negative active material, negative plate and lithium ion battery
CN112002883A
Silicon negative electrode material of lithium ion battery and preparation method and application thereof
CN112614976A
Solid-state silicon lithium battery positive electrode material and preparation method thereof
CN113488627A
Cited By
Method for preparing silicon-based composite material in one step and application of silicon-based composite material in all-solid-state battery
CN120288775A